Employee Stock Purchase Plans: Gift or Incentive? Evidence from a Multinational Corporation - Alex Bryson; Richard B. Freeman (Institute for the Study of Labor (IZA), 2014)
Many large listed firms offer workers the opportunity to buy shares in the firm at discounted rates through employee stock purchase plans (ESPP). The discounted rate creates a gift exchange, where the firm hopes that workers who accept the gift reciprocate with greater loyalty and effort. But ESPPs diverge from standard gift exchange or efficiency wage models. Employees have to invest some of their own money by purchasing shares at the discounted rate to accept the gift. A sizeable number choose to reject the gift. In addition, the value of the ESPP gift varies with the share price and thus with the performance of the firm and the effort of workers in total. For workers who buy subsidized shares, an ESPP sets up a group incentive pay system analogous to profit sharing, all-employee stock options, or an employment ownership scheme that makes part of workers' compensation depend on company performance. Using data from the UK establishments of a multinational firm that places its ESPP at the heart of its employee compensation system, we compare the workplace behaviour of employees who join the ESPP with that of observationally equivalent workers who do not join the plan. We find that workers who purchase shares at subsidized prices work harder for longer hours and have lower quit and absence rates than workers who do not join the plan, but are no more involved in co-monitoring the performance of fellow employees than non-Plan members. We also find perceptions of peers' Plan participation influences workers' behaviour. ESPP joiners socialise more with colleagues outside work: this greater sense of social identity with colleagues, predicted under some gift exchange models, lowers their costs of work effort and may explain why they are more productive than those who do not join the ESPP. These findings highlight the distinct place of subsidized share purchase schemes in the spectrum of gift exchange and group incentive pay systems.
Keywords: J24; J33; J54; J63; M52; 330; share ownership; job search; quits; sickness absence; effort; gift exchange; incentives